2018
DOI: 10.1111/php.13065
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Prospective Study Assessing the Combination of Photodynamic Therapy and Proton Radiation Therapy: Safety and Outcomes When Treating Malignant Pleural Mesothelioma

Abstract: Malignant pleural mesothelioma remains difficult to treat, with high failure rates despite optimal therapy. We present a novel prospective trial combining proton therapy (PT) and photodynamic therapy (PDT) and the largest-ever mesothelioma PT experience (n = 10). PDT photosensitizers included porfimer sodium (2 mg-kg−1; 24 h drug-light interval) or 2-[1-hexylox-yethyl]-2-devinyl pyropheophorbide-a (HPPH) (4 mg m−2; 48 h) with wavelengths of 630 nm to 60Jcm−2 and 665 nm to 15–45Jcm−2, respectively. With a media… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 84 publications
0
13
0
Order By: Relevance
“…Fortunately, a formulation modification can add lysosomes to the targeting profile of BPD, as described below. Other groups have established the ability of PDT to enhance the efficacy of chemotherapy and ionizing radiation [35,36,37]. There have been recent advances relating to the ability of PDT to promote immunologic responses [38,39,40].…”
Section: New Photosensitizers and Combinationsmentioning
confidence: 99%
“…Fortunately, a formulation modification can add lysosomes to the targeting profile of BPD, as described below. Other groups have established the ability of PDT to enhance the efficacy of chemotherapy and ionizing radiation [35,36,37]. There have been recent advances relating to the ability of PDT to promote immunologic responses [38,39,40].…”
Section: New Photosensitizers and Combinationsmentioning
confidence: 99%
“…1 Here we present general guidelines for this approach. 25 Pencil beam scanning (PBS) proton therapy may be the optimal proton delivery choice for MPM. PBS involves the use of steering magnets to "paint" proton beam "spots" layer by layer over the target volume, which can provide better dose coverage than passive scattering proton therapy for volumes of complex shape and also allows the delivery of intensity-modulated proton therapy (IMPT), 26 which is especially useful for treating the large, irregularly shaped volumes involved in hemithoracic radiotherapy after EPP or whole pleural radiotherapy after extended P/D.…”
Section: Proton Beam Therapymentioning
confidence: 99%
“…No patient experienced Common Terminology Criteria for Adverse Events, version 4, grade 2 or higher acute or late toxicity. 25 Investigators from the University of Washington School of Medicine reported outcomes for three patients with MPM treated with PBS to 54 to 66 Gy (RBE) after EPP in contrast with the outcomes of to proton therapy delivered to intact lungs. Compared with volumetricmodulated arc therapy photon plans, PBS produced lower doses to organs at risk.…”
Section: Proton Beam Therapymentioning
confidence: 99%
“…There continues to be support for three major PDT research groups (University of Pennsylvania, Massachusetts General Hospital/Harvard and Roswell Park Cancer Center). There are implications for use of PDT in otherwise poorly‐responsive tumors, for example, pancreatic cancer and mesothelioma . At this point, an appreciation for what PDT can do appears to be limited to a few centers in the US.…”
Section: Discussionmentioning
confidence: 99%